2012
DOI: 10.1007/s00774-012-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

An altered hormonal profile and elevated rate of bone loss are associated with low bone mass in professional horse-racing jockeys

Abstract: Horse-racing jockeys are a group of weight-restricted athletes, who have been suggested as undertaking rapid and extreme weight cycling practices in order to comply with stipulated body-mass standards. The aim of this study was to examine bone mass, turnover and endocrine function in jockeys and to compare this group with age, gender and body mass index matched controls. Twenty male professional jockeys and 20 healthy male controls participated. Dual energy X-ray absorptiometry scans and early morning fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…It is further possible that the endocrine suppression during low energy availability was blunted by increased circulating concentrations of binding proteins, which were not assessed in this study. Dolan et al reported that male jockeys, a group known to undergo repeated periods of energy deficiency, demonstrated normal total testosterone but elevated sex hormonebinding globulin concentrations, resulting in reduced testosterone bioavailability when compared to matched controls (Dolan et al, 2012). Future controlled experiments are needed to determine how the magnitude and duration of the energy deficit, basal leptin concentrations and changes in binding proteins modulate the suppression of metabolic hormones during energy deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is further possible that the endocrine suppression during low energy availability was blunted by increased circulating concentrations of binding proteins, which were not assessed in this study. Dolan et al reported that male jockeys, a group known to undergo repeated periods of energy deficiency, demonstrated normal total testosterone but elevated sex hormonebinding globulin concentrations, resulting in reduced testosterone bioavailability when compared to matched controls (Dolan et al, 2012). Future controlled experiments are needed to determine how the magnitude and duration of the energy deficit, basal leptin concentrations and changes in binding proteins modulate the suppression of metabolic hormones during energy deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Because men have to invest less energy for reproductive purposes than women (Bronson, 1985), it is not surprising that the male reproductive system appears more robust against energy deficiency. Other health-related outcomes of chronic energy deficiency, such as impaired bone health, have also been reported in exercising men (Campion et al, 2010;Dolan et al, 2012). However, the underlying mechanisms, the dose-response relationship with energy availability and the acute vs chronic nature of these effects remain Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of menstrual dysfunction and impaired bone health in female elite athletes competing in weight-sensitive sports is higher than that among female athletes representing sports that are less sensitive to the effects of body weight (Coelho et al, 2010;Rauh et al, 2010). In addition, it is evident that energy deficiency, suppressed hormonal activity, and reduced bone mineral density (BMD) also affect male athletes (Dolan et al, 2012;Hetland et al, 1993;Smathers et al, 2009). For example, Smathers et al (2009) found that 9% of male competitive cyclists and 3% of age-and body mass-matched control subjects were classified as osteoporotic, and as many as 25% of the cyclists had low BMD compared with 10% of the control subjects.…”
Section: Health Consequences Of Energy Deficiency Disordered Eatingmentioning
confidence: 99%
“…14 It is well recognized in the literature that the suppression of metabolic hormones secondary to prolonged energy deficiency is associated with unfavorable health outcomes, such as impaired reproductive, bone, and cardiovascular health. [16][17][18][19] The suppression of testosterone and IGF-1, which both possess strong anabolic properties, may further result in unfavorable alterations in fuel utilization and more importantly, in the long-term loss of muscle mass and muscle function. 20,21 Therefore, it remains unclear whether strategies to increase dietary energy intake during prolonged ultra-endurance exercise in efforts to prevent energy deficiency could also attenuate the suppression of metabolic hormones, and minimize the detrimental effects of energy deficiency in the long-term.…”
Section: Introductionmentioning
confidence: 99%